The roles and functions of language in human life in the era of industrial revolution 4.0 and the twenty-first century - Izzati Khairina; Riris Marisi Rosinda Simarmata; An Nayla Al Farohah; Silvina Noviyanti; Nazurty Nazurty (Privietlab, 2025)
The rapid development of technology in the era of the Industrial Revolution 4.0 and the twenty-first century has significantly transformed the way humans communicate, think, and interact. Language, as the primary medium of communication, has expanded beyond transmitting messages. It now serves as the foundation for digital identity formation, media literacy, and mastery of twenty-first-century competencies, including critical thinking, creativity, collaboration, and communication. This study aims to analyze the roles and functions of language in modern human life and identify the linguistic challenges that emerge in the digital era. Using a literature study method with a qualitative descriptive approach based on document analysis following Sugiyono’s guidelines, this research reveals that language holds a strategic position in education, society, and technology. Language supports information processing, social relationship building, and individual adaptation to global environments. However, several challenges arise, such as the excessive use of abbreviations and digital symbols that lead to ambiguity, low levels of digital literacy, and increasing risks of misinformation and misinterpretation in cross-cultural communication. The study concludes that strengthening language and digital literacy is essential to ensure that individuals can effectively adapt to technological changes and maintain ethical, clear, and meaningful communication in the digital age.